¿Qué tan “amazónicas” son las lenguas kawapana? Contacto con las lenguas centro-andinas y elementos para un área lingüística intermedia - Valenzuela, Pilar M. (2015)
The kawapana linguistic family of northeastern Peru is formed by shiwilu and shawi languages, also known as Jebero and Chayahuita respectively. Ordinarily, it is usually categorize kawapana languages as “Amazonian” linguistic entities. However, this study shows that they share significant grammatical similarities to the central-andean quechua and aymara families, as well as other languages of the relatively nearby lowlands. This convergence would be the result of linguistic changes induced by contact or indirect dissemination. In addition to unveiling the complex grammatical profile of languages kawapana, this study provides evidence in favor of an intermediate language area between the Amazon and the Andes, of which kawapana languages form part.